Leon Petrażycki i rozwój nauk o politykach publicznych - Oniszczuk, Jerzy (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Studies on public policies are vital for law-making and public policies in the rule of law state since such studies ensure thoughtful actions in these fields. Some roots of public policies can be found in the works of Leon Petrażycki, legal theorist, sociologist and philosopher. He promoted creating an intelligent, scientific approach to policies by means of so called scientific legal policy. In 21st century a postulate of Petrażycki was followed and enhanced by technological revolution in the form of global cyber world which influenced all fields of human life. And started to decide “intelligently” on the future of the society. Compound results of self-learning programmes of artificial intelligence (AI) led to conviction that to make the decisions of public policy rational it is necessary to support them scientifically. As science tries to understand incessant development in the field of digital programmes. Therefore, as a result of this progress, public policy and law-making aimed at social problem solving, are no longer an issue of politicians’ intuition or wishes. Concepts of social transformations by means of bills and implemented according to the values of the politicians are questioned. As well as questioned is an old rule stating that doctrines are constituted independently by representatives of a nation in conformity of its will. Dissemination of AI entails some serious ethical and legal issues. It can be assumed that humans in this era of technology will keep control over the processes of transformations as long as they will decide on what is morally accepted. Anyway, in the world of a rule shared between programmes/machines (AI) and people, in the world of the new attitude toward “the network of things” (that is: their real service to a man not the other way round) we are facing a legal revolution. As for science and politics, the question is protection of humanity.